2023
DOI: 10.3390/antiox12030717
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Viable and Heat-Inactivated Lactobacillus rhamnosus GG Administration on Oxidative Stress and Inflammation in Diet-Induced NAFLD in Rats

Abstract: Oxidative stress and inflammation are well-known triggers of NAFLD onset and progression. The aim of this study is to compare the potential benefits of a viable probiotic (Lactobacillus rhamnosus GG) and its parabiotic (heat-inactivated) on oxidative stress, inflammation, DNA damage and cell death pathways in the liver of rats featuring diet-induced NAFLD. The consumption of the steatotic diet led to increased final body and liver weights, higher hepatic triacylglycerol content, altered serum transaminase leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…The results of this study were consistent with the above study ( Hassan et al, 2020 ), L. plantarum ATCC14917 can reverse the changes in the structure of the gut microbiota induced by the HFD, notably the major bacterial phylum. In recent years, many studies have shown that probiotics can regulate intestinal flora to prevent intestinal flora imbalance, improve intestinal barrier function, reduce oxidative stress and inflammation, and improve lipid metabolism and NAFLD ( Cao et al, 2022 ; Hu et al, 2022 ; Arellano-García et al, 2023 ; Shin et al, 2023 ; Wang et al, 2023 ; Zhao et al, 2023 ). In addition, there are several studies on the effects of different probiotics on improving NAFLD in clinical trials ( Arellano-García et al, 2022 ; Noormohammadi et al, 2023 ; Zhou et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study were consistent with the above study ( Hassan et al, 2020 ), L. plantarum ATCC14917 can reverse the changes in the structure of the gut microbiota induced by the HFD, notably the major bacterial phylum. In recent years, many studies have shown that probiotics can regulate intestinal flora to prevent intestinal flora imbalance, improve intestinal barrier function, reduce oxidative stress and inflammation, and improve lipid metabolism and NAFLD ( Cao et al, 2022 ; Hu et al, 2022 ; Arellano-García et al, 2023 ; Shin et al, 2023 ; Wang et al, 2023 ; Zhao et al, 2023 ). In addition, there are several studies on the effects of different probiotics on improving NAFLD in clinical trials ( Arellano-García et al, 2022 ; Noormohammadi et al, 2023 ; Zhou et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the yogurt-derived Lactobacillus plantarum Q16 reduced the hepatic lipid content and improved the hepatic energy metabolism via the fibroblast growth factor 21 (FGF21)/adiponectin/AMPKα/peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC-1α) signaling pathway [ 20 ]. In addition, Lactobacillus rhamnosus GG administration prevented NAFLD in rats by increasing their resistance to oxidative stress and inflammation [ 21 ]. Additionally, the treatment of Lactobacillus lactis and Pediococcus pentosaceus ameliorated NAFLD progression in mice by improving the main metabolic features, like short chain fatty acids (SCFAs), bile acids (BAs), and tryptophan metabolites, suggesting that the probiotics reprogrammed the gut microbiome and metabolic environment via the gut–liver axis [ 32 ].…”
Section: Probiotics and Nonalcoholic Fatty Liver Diseasementioning
confidence: 99%
“…Probiotics play a crucial role in maintaining or restoring the homeostasis of gut microbiota, representing a key factor in alleviating NAFLD and preserving the host’s overall health status ( Kaufmann et al, 2023 ). Among the identified probiotics, Lactobacillus and Akkermansia have demonstrated the ability to mitigate liver damage, metabolic abnormalities in the host, and disruptions in the gut microbiota caused by a high-fat diet (HFD) ( Cani and de Vos, 2017 ; Arellano-Garcia et al, 2023 ). However, the cultivation of these two species is challenging, and their therapeutic efficacy may be influenced by environmental factors.…”
Section: Introductionmentioning
confidence: 99%